Dana Desa Dan Pengaruhnya Terhadap Pendapatan Asli Desa Di Kabupaten Pesawaran - Kiki Ambarwati; Dewangga Nikmatullah; Indah Listiana (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
The Birth of the Village Law No. 6 of 2014 concerning Villages makes villages have an important role for regional autonomy, and village fund policies. With the existence of village funds as a source of village income originating from APBN transfers, sources of village original income (PADes) can be optimally supported if management is carried out properly. This study aims to determine the effect of village funds on PADes and analyze the use of village funds for village development activities. The study was conducted in a survey in 12 villages using descriptive analysis and paired sample T test. The results showed that there was no difference in PADes before and after village funds were given. This means that the presence or absence of village funds given to villages does not affect the increase in PADes received. 70 percent of villages in Pesawaran Regency the amount of PADes received is still zero or even decreased from the previous year. The management of village funds still has many shortcomings, both in the form of transparency to orderly rules ranging from independent villages to underdeveloped villages. 90 percent of villages utilize village funds for physical development activities and only Sukaraja Village (independent villages) which is larger utilize village funds for community development/empowerment activities.